Corporate Enterprenerurship di sektor Pelayanan Publik Studi Kasus: Badan Pelayanan Perizinan Terpadu Kota dan Kabupaten Bandung - Astri Ghina, Dwi Larso (ITB, 2011)
Corporate Entrepreneurship (CE) is an important concept to reform within bereaucracy carried out in order to enhance effciency and effectiveness of Goverment's performance in providing an excellent service to the society. This study examinated the relationship between entrepreneurial orientation and entrepreneurial leadership on job satiscation and consumers' satisfaction. The instrumnt used to measure Corporate Entrepreneurship is Entrepreneurial Orientation Survey (EOS) and Entrepreneurial leadrship Questionnaire (ELQ). The method used to undertand the phenomenon was the survet of 204 respondents who work for public service sector within badan pelayanan perizinan terpadu (BPPT) at Bandung City and Regency. Path Analysis was used to test the influence of entrepreneurial orientation and entrepreneurial leadrship on job satisfaction and consumers' satisfaction. It means that the higher of entrepreneurial orientation and entrepreneurial leadership then the higher of government's performance, evaluated from job satisfaction and society's satisfaction. According to EOS and ELQ results. there was a significant diference in characteristics between BPPT at Bandung City and Regency, evaluated from entrepreneurial orientation, entrepreneurial leadrship, job satisfaction and society's satisfaction